2014
DOI: 10.1097/md.0000000000000044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Intake and Potassium Supplementation on Serum Renalase Levels in Chinese Adults

Abstract: Renalase, a recently discovered enzyme released by the kidneys, breaks down blood-borne catecholamines and may thus regulate blood pressure (BP). Animal studies have suggested that high levels of dietary salt might reduce blood and kidney renalase levels. We conducted a randomized trial to assess the effects of altered salt and potassium intake on serum renalase levels and the relationship between serum renalase levels and BP in humans.Forty-two subjects (28–65 years of age) were selected from a rural communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 31 publications
1
32
0
3
Order By: Relevance
“…In addition, increased dietary sodium inhibits renalase protein expression in rats subjected to subtotal nephrectomy, as well as in Dahl salt-sensitive rats [7]. More recently, we found that serum renalase levels increased with a low-salt diet and decreased with a high-salt diet in Chinese subjects [8]. High dietary salt has also been shown to upregulate urinary renalase levels and activity in both 3/4 nephrectomized (3/4nx) and sham rats [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, increased dietary sodium inhibits renalase protein expression in rats subjected to subtotal nephrectomy, as well as in Dahl salt-sensitive rats [7]. More recently, we found that serum renalase levels increased with a low-salt diet and decreased with a high-salt diet in Chinese subjects [8]. High dietary salt has also been shown to upregulate urinary renalase levels and activity in both 3/4 nephrectomized (3/4nx) and sham rats [9].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies demonstrated that increased potassium intake remarkably alleviated high dietary salt-induced increases in BP [8,13]. Clinical trials have also shown that long-term potassium supplementation may lower the risk of cardiovascular disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…Human diseases in which the tissue and blood levels of renalase are decreased are essential hypertension, chronic kidney disease, and preeclampsia [4][5][6] . In addition, renalase decreases even when salt intake is high or when there is a lack of potassium intake 7) . The abovementioned diseases or lifestyle habits have hypertensive symptoms as a clinical symptom or health risk.…”
Section: Introductionmentioning
confidence: 99%
“…This questions the proposed role of renalase in the regulation of blood pressure. Taken together, the results obtained by the Chinese team [9,11] indicate different behavior of serum and urinary renalases under conditions of altered dietary salt supplementation, and suggest the involvement of different mechanisms of salt-dependent regulation of renalase levels in biological body fluids. …”
mentioning
confidence: 88%
“…Interestingly, the same Chinese authors found opposite changes in serum renalase levels, which increased in Chinese subjects in response to a low-salt diet and decreased in response to a high-salt diet [11]. This questions the proposed role of renalase in the regulation of blood pressure.…”
mentioning
confidence: 94%